JOB QUALITY AND IMPACT OF RETIREMENT ON HEALTH BEHAVIORS: RESULTS FROM A NATIONWIDE TEN-YEAR PANEL SURVEY IN JAPAN. (11th November 2018) - Kan, M
Abstract: We investigate how effects of retirement on the change in health behaviors are different across individuals with different job, weekly working hours, and level of satisfaction to their jobs. We focus on the immediate effects of retirement in order to understand the influence of the quality of previous job. Using ten waves of the Longitudinal Survey of Middle-aged and Elderly Persons in Japan (2005–2014), we considered four health behaviors: current smoking, number of cigarettes smoked, heavy alcohol drinking, and leisure-time physical activity. Outcome measures are made of difference between current status and previous status: i.e. we subtract the value at time t-1 from the value at time t. Job qualities are described with four aspects: occupational category; whether satisfied with their work content; and whether satisfied with their work-site interpersonal relation; and hours worked per week in the previous year. Results show that retirees from professional or managerial jobs decreased the probability of heavy alcohol drinking and leisure-time physical activity. Retirees who were not satisfied with their job content when they worked quit smoking after the retirement. Hours worked per week are the factors that explain smoking cessation and initiation of physical activity after retirement. It is more likely for workers who worked long hours quit smoking and decrease the number of cigarettes after retirement. The results indicate that effects of retirement on health behaviors are not uniform. Therefore health promotion to retirees should take into account a quality of their previous job.